Detection of changes in the structure and distribution map of triacylglycerol in fatty liver model by MALDI‐SpiralTOF. Issue 1 (19th February 2014) - Nishikawa, Kahoko; Hashimoto, Masahiro; Itoh, Yoshiyuki; Hiroi, Sadayuki; Kusai, Akihiko; Hirata, Fumihiko; Sakamoto, Toshihisa; Iwaya, Keiichi
Abstract : Matrix‐assisted laser desorption/ionisation spiral orbit‐type time‐of‐flight mass spectrometry (MALDI‐SpiralTOF) can analyse lipid profiles and characterise lipid structure. Imaging mass spectrometry (IMS) also provides distribution maps of selected m / z values. Here, we investigated triacylglycerol (TG) structure and distribution using these technologies to estimate mouse fatty liver. The distribution and intensity of the most intense mass spectrum ion was indicated by IMS at m / z 881.7 (52:2). Analysis using MS/MS showed a structural change between liver TG and dietary TG. These findings suggest that MALDI‐SpiralTOF is a powerful tool for clinical screening and estimating fatty liver. Abstract : MS/MS and imaging mass spectrometry analysis (IMS) were used to estimate mouse fatty liver. Triacylglycerol (TG) structure and distribution were measured using MS/MS and IMS. The most intense mass spectrum ion was indicated by IMS at m / z 881.7 (52:2). MS/MS showed a structural change between liver TG and dietary TG. MALDI‐SpiralTOF with IMS could be a powerful tool for clinical screening of fatty liver.